Gene expression and clinical outcomes after dietary treatment for eosinophilic esophagitis: a prospective study. Issue 10 (5th June 2022) - de Rooij, Willemijn E.; Diks, Mara A. P.; Warners, Marijn J.; Ampting, Marleen T. J. Van; van Esch, Betty C. A. M.; Bredenoord, Albert J.
Abstract: Background: Eosinophilic esophagitis (EoE) is an allergen‐mediated disease and elimination diets have proven to be effective to obtain clinical and histological remission. However, the effect of elimination diets on specific EoE transcripts and their clinical correlates is relatively unknown. The main aim of the study was to evaluate the effect of dietary treatment (four‐food elimination diet [FFED]) with or without addition of amino acid‐based formula (AAF) on a variety of pro‐/anti‐inflammatory, epithelial/barrier function and remodeling/fibrosis‐related markers of disease activity and clinical correlates (eosinophils, symptoms, and endoscopic signs) in adult EoE patients. Methods: We conducted an analysis of biopsy samples and data collected during a randomized controlled trial with an elimination diet in adult patients with active EoE (≥15 eosinophils [eos] per high‐power field [hpf]). Demographics, symptoms (SDI‐score), endoscopic signs (EREFS) and peak eosinophil counts/hpf were recorded at baseline and after 6 weeks of treatment. Transcripts of 10 indicated genes were measured (qPCR) and compared to clinical correlates at baseline and after treatment. Key Results: Forty patients (pooled FFED + FFED + AAF) (60% male, age 34.5 (interquartile range [IQR] 29–42.8 years) completed the diet. Peak eosinophil counts/hpf, symptoms and endoscopic signs were significantly decreased after 6 weeks dietary treatment. DSG‐1 levels were significantly upregulated from baseline to week 6, whereas IL‐13, CAPN‐14, IL‐5, IL‐10, CCL‐26, POSTN, TSLP, CPA‐3, and TGF‐β were significantly downregulated after 6 weeks of diet (all; <0.01). Prior to treatment, upregulation of CAPN‐14 and lower levels of DSG‐1 were associated with clinical fibrotic phenotypes, whereas upregulation of IL‐10 was linked to food impaction phenotypes. Conclusion: These findings strongly suggest that elimination diets, besides a clinical and histological response, are associated with a broad transcriptional response at the level of the esophageal epithelium. Abstract : Gene expression and clinical outcomes after dietary treatment: a prospective study.